1978
DOI: 10.3171/jns.1978.48.3.0443
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral cerebral atrophy with thalamic tumor of childhood

Abstract: A case of cerebral tumor with ipsilateral cerebral hemiatrophy is presented and five previously reported cases are reviewed. The etiology of this entity is discussed on the basis of the symptomatological and clinicopathological findings noted in these six cases. It is suggested that ipsilateral cerebral hemiatrophy is due to thinning of the cerebral cortex with degeneration and disappearance of ganglion cells, demyelination in the subcortex, and destruction of axons. The mechanism proposed for ipsilateral cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…12 Although the remote secondary thalamic reaction after primary ischemic or traumatic cortical damage is a well-known phenomenon, there are only very few reports on secondary reactions in those remote brain areas caused by brain tumors. 13,14 This study was undertaken to investigate whether D-cis-[ 18 F]FPro is able to show secondary reactions in remote brain areas induced by brain tumors and to further explore the uptake behavior of this tracer in neoplastic lesions. H]Thymidine ([ 3 H]thymidine) was used as a reference, which allows a direct comparison of D-cis- [ 18 F]FPro uptake in relation with cell proliferation in the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…12 Although the remote secondary thalamic reaction after primary ischemic or traumatic cortical damage is a well-known phenomenon, there are only very few reports on secondary reactions in those remote brain areas caused by brain tumors. 13,14 This study was undertaken to investigate whether D-cis-[ 18 F]FPro is able to show secondary reactions in remote brain areas induced by brain tumors and to further explore the uptake behavior of this tracer in neoplastic lesions. H]Thymidine ([ 3 H]thymidine) was used as a reference, which allows a direct comparison of D-cis- [ 18 F]FPro uptake in relation with cell proliferation in the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the proposed mechanism for the cerebral hemiatrophy was that the thalamic tumor caused degeneration and disappearance of the thalamic ganglion cells and nerve fibers. This caused secondary Wallerian degeneration of projecting fibers from the thalamus, as well as retrograde degeneration of corticothalamic neurons, resulting in extensive atrophy of the cerebral cortex and subcortical tissue (15). In ML,brain atrophy without therapy is rare (16), and, to our knowledge, MLshowing marked, diffuse brain atrophy has not previously been reported.…”
Section: T-lymphoma Showing Marked Brain Atrophymentioning
confidence: 85%
“…109 patients with germinoma of the basal ganglia have been reported in the literature (table 1) [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40]. There is a male predominance (male:female = 90:7) and the age at diagnosis is between 7 and 40 years (mean age 12.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…Kwak et al [14]suggested that ipsilateral cerebral hemiatrophy was due to secondary wallerian degeneration of afferent fibers from the thalamus and basal ganglia and retrograde degeneration of efferent fibers caused by destruction and disappearance of ganglia cells and nerve fibers resulting from tumor invasion and infiltration.…”
Section: Discussionmentioning
confidence: 99%